Beginning Spring 2 From Novice to Professional - Minter, Dave.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2007)
Spring has made a remarkable rise since its conception in 2002. Users find Spring the ideal framework to build their applications in J2EE environments. Beginning Spring 2 is the first Spring–authorized book that takes you through the first steps of using Spring, and requires no prior J2EE experience. It discusses relevant integrated technologies that you should be aware of, and illustrates how Spring makes using them easier. The book teaches the correct usage of Spring in applications, and lowers the learning curve on J2EE standards. It covers useful features of Spring without delving too far into complicated features. The authors take advantage of less complex alternatives whenever possible, and shows how Spring can make you more productive in complicated environments where J2EE technologies need to be applied. The book covers the complete Spring web tools portfolio and deals with persistence and transaction management. It also introduces 3–tier application design and how to test these designs.
An Introduction to Spring -- Presenting the Sample Application -- The Heart of Spring: Inversion of Control -- Data Access -- The Service Layer, Transaction Management, and AOP -- Web Applications -- Security -- Sending E-mail -- Remoting -- Testing.
Keywords: Java (Computer program language).; Software engineering; Java; Software Engineering/Programming and Operating Systems